A Neurocognitive Perspective on the Forms and Functions of Autobiographical Memory Retrieval - Sheldon, Signy; Fenerci, Can; Gurguryan, Lauri (Frontiers in Systems Neuroscience, 2019)
Autobiographical memory retrieval involves constructing mental representations of personal past episodes by associating together an array of details related to the retrieved event. This construction process occurs flexibly so that the event details can be associated together in different ways during retrieval. Here, we propose that differences in how this association occurs support a division in autobiographical remembering. We first review theories of autobiographical memory organization that suggest that episodic details of an experience are processed along a gradient of abstraction. This organization allows for the same autobiographical event to be recalled as either a conceptualized or perceptually-based episodic memory. We then use neuroimaging evidence to show how this division within episodic autobiographical memory is also present in the brain, both at a network level and within the hippocampus. Specifically, we suggest that the anterior and posterior hippocampus are obligatorily tuned towards constructing conceptual versus perceptual episodic representations of autobiographical memories. Finally, we discuss the directive purpose of this proposed division of episodic remembering by reviewing decision scenarios that benefit from recalling the past as a conceptual versus a perceptual episode. Conceptual remembering is useful to guide ambiguous decisions that have yet to be encountered whereas perceptual remembering is useful to guide decisions for well-structured tasks that have been previously experienced. We emphasize that the ability to shift between conceptual and perceptual forms of remembering, by virtue of hippocampal specialization, during decision-making and other memory-guided actions is the key to adaptive behaviour.